Proteomic-based evidence for adult neurogenesis in birds and mammals as indicated from cerebrospinal fluid - Voukali, Eleni; Vinkler, Michal (Neural regeneration research, 2022)
Adult neurogenesis is the life-long process of neural stem cell proliferation, differentiation into neurons, migration, and incorporation into the existing neuronal circuits. After decades of research, it is now widely accepted that mammals and birds retain the capacity to regenerate neurons even after their subadult ontogeny. Cerebrospinal fluid participates in the regulation of the neurogenic niches of the vertebrate brain through signaling pathways not fully elucidated. Proteomic studies of cerebrospinal fluid have the potential to allow the in-depth characterization of its molecular composition. Comparative studies help to delineate those pathways that are universally critical for the regulation of neurogenesis in adulthood. In this review, we performed literature-based data mining in studies using liquid chromatography-tandem mass spectroscopy that analyzed cerebrospinal fluid samples from healthy adult humans (Homo sapiens); mice (Mus musculus); sheep (Ovis aries); chickens (Gallus gallus); and two parrot species, the budgerigar (Melopsittacus undulatus) and cockatiel (Nymphicus hollandicus). We identified up to 911 proteins represented in cerebrospinal fluid, involved in various pathways regulating adult neurogenesis. However, only 196 proteins were common across humans, mice, and birds. Pathway components involved in nervous system development, cell migration, and axonal guidance were commonly evident in all species investigated so far. Extensive bioinformatic analysis revealed that the universally over-represented pathways involved L1 cell adhesion molecule protein interactions, cell-adhesion molecules, signals regulating extracellular matrix remodeling, regulation of insulin growth factor signaling, axonal guidance, programmed cell death, immune signaling, and post-translational modifications. Most of the reported proteins are part of extracellular vesicles enriched in cerebrospinal fluid. However, the information presently available is still highly fragmentary, and far more questions persist than are answered. Technological advances will allow cerebrospinal fluid comparative proteomic research to delve into the fundamental processes of adult neurogenesis and eventually translate this research into any regenerative interventions.
Keywords: parrots; mammals; human; adult neurogenesis; comparative proteomics; mass spectrometry; chicken; birds; cerebrospinal fluid